GE_GERICHTE P/4264/2013 vom 23. Dezember 2014 - GE Cour de justice (2014)
LÉSION CORPORELLE; VOIES DE FAIT; INJURE; MENACE(DROIT PÉNAL); LOCATAIRE; FIXATION DE LA PEINE; DOMMAGES-INTÉRÊTS; INDEMNITÉ(EN GÉNÉRAL) | CP.123.1; CP.177.1; CP.180.1; RTP.11.1; CP.47; CP.19.2; CP.49.1; CP.73; CO.41; CPP.433.1.A